Islamic Bank Financial Performance Analysis: Influence and Causes - Muhammad Rifky Santoso (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Analysis of the financial performance of Islamic banks is mostly done by experts. This analysis uses many models, such as liquidity. In addition to assessing the financial performance of the Islamic bank itself, this financial performance analysis also refers to its influence on other factors such as economic growth. By using a literature study, this article analysis what influences and is influenced by the financial performance of Islamic banks. This article finds that the financial performance of Islamic banks influences external factors such as economic growth and internal factors such as credit risk. This financial performance is also influenced by external factors, such as economic growth, and internal ones, such as CSR disclosure. The financial performance of Islamic banks is also used to compare it with the performance of conventional banks and fellow Islamic banks in different countries. Each researcher in the sampled article uses a different analytical method according to his research objectives. Islamic banks have a unique performance analysis method that does not exist in conventional banks, namely financing measurement using non-profit loss-sharing and profit loss-sharing schemes